Physical, chemical and sensory properties of kiwi as influenced by drying conditions - Correia, Paula (2017)
The present study aimed at studying the effect of convective air drying on some physical, chemical and sensory properties of kiwi (Actinidia deliciosa L.) samples. The kiwi samples were dried in thin layer convective chambers set to constant temperatures at 50ºC, 60ºC, 70ºC and 80ºC. The fresh samples and the dried samples were analysed for moisture, water activity, vitamin C, total phenolic compounds, antioxidant activity, colour and texture. Also the different dried samples were submitted to a sensory evaluation. It was concluded that drying of kiwi importantly decreased the contents of some bioactive components such as vitamin C and phenolic compounds as well as the antioxidant activity. Moreover, the negative impact was higher at higher drying temperature. Drying also altered the colour towards a lower intensity of the green colouration and a higher intensity of the yellow. In what concerns the textural properties, drying produced important alterations, however the influence of temperature was not visible. Regarding the sensory evaluation, it was not possible to clearly distinguish the samples analysed, particularly in what related to the global appreciation. Still, it was possible to establish the sensory profiles of the dried samples, and the attributes that varied most among them were colour intensity, crunchiness and hardness.